Evaluation of microbiological epidemiology and clinical characteristics of maternal bloodstream infection: a 10 years retrospective study - Guo, Junfei; Wu, Yongbing; Li, Huan; Deng, Wenyu; Lai, Weiming; Gu, Chunming; Luo, Mingyong (Frontiers in Microbiology, 2024)
[Objective] Although the incidence of bloodstream infection (BSI) during pregnancy is relatively low, it may lead to unfavourable outcomes. The aim of our study was to analyse the clinical and microbiological characteristics of maternal bacteraemia and to assess maternal and fetal outcomes. [Methods] Our study was a retrospective study conducted in a tertiary women and children’s hospital in Guangzhou, China, from 2013 to 2022. Data were extracted from medical record and laboratory information system. The participants were divided into groups, and the difference between the groups was analysed. [Results] The incidence of maternal BSI during 10-year study period was 10.2 cases/10,000 maternities, with a peak found from 2014 to 2016. Escherichia coli (48%) was the predominant causative pathogen, followed by Streptococcus agalactiae (13%). Gestational diabetes mellitus (GDM) (15%) was the most common underlying condition among maternal BSI episodes. Urinary tract (13%) and genital tract (28%) were the predominant source of BSI. About 14% of neonates were infected, and BSI was the most common type of infection. E. coli was the predominant pathogen in mother-neonate pairs with concurrent BSI. Premature rupture of membranes (PROM, OR:4.68) and preterm birth (OR:3.98) were the risk factors predicting neonatal infection. More than 85% of the E. coli were resistant to ampicillin (AMP) and 50% of the E. coli were extended-Spectrum β-lactamase (ESBL)-producing bacteria. [Conclusion] Maternal BSI is a rare event, but continuous monitoring on the aspects of pathogen composition, antimicrobial resistance characteristics and risk factors for adverse outcomes remains necessary to further reduce poor outcomes and mitigate bacterial resistance.